Typology of Renaissance Palazzo: Lifestyle and Design of the Interior. The Example of Palazzo Davanzati - Dunina, Maria V. (Actual Problems of Theory and History of Art, 2014)
Built in Florence in the late Trecento, Palazzo Davanzati belongs to the period of transition from the medieval architecture to the architecture of Renaissance. Social changes that took place at that time caused a new attitude towards the way of life and are reflected in the secular building. Palazzo shows the world of its owners — a huge merchant family — who had adopted the courtly lifestyle. It is evident that there formed the type of palazzo that unified the functions of a feudal castle and a house of a rich popolano and drew on the experience of the Roman insula, which would be important for the development of the architecture of the 15th c. Not being fully Renaissance palace, palazzo Davanzati is still corre-sponding to the ideals of the Renaissance theorists, unifying fortification with regularity of forms and hu-manistic orientation. Comparison with earlier and later samples demonstrates an innovative functional architectural design and reveals the role of the building in the process of development of the house building. Using literary and pictorial sources it is possible to estimate the planning and reconstruct the furnishing of the palace. We study the way that already in the 14th c. allowed to arrange rationally different apartments assigned for different needs and to give them an appropriate decoration.